The institutionalisation of geography in New Zealand, an interpretation : a thesis submitted for the degree of Doctor of Philosophy, Department of Geography, Massey University - Hammond, John Gilbert (Massey University, 1992)
When geography, as an abstract form of knowledge, becomes identified with a set of practices involving agents, it assumes a coherent structural form and may be said to have become institutionalised. Institutionalisation, however, is a process in which the interactions between structures and agents continue to evolve through contest. An epochal account of academic geography supports any understanding of what has taken place in New Zealand geography because it legitimates a theoretical placement of geographical inquiry in the setting of global capitalism. Critical institutional theory, as an analytical tool, is propelled by the focusing questions of 'Why'? 'For Whom'? and To Whose Advantage'? It is naive to assume that the overall conduct of institutional life is anything but a contested process, the site of ideological, methodological, personal and administrative differences. To complete the theoretical discussion, the need to elicit a processual account of institutionalising phenomena mandates a consideration of oral history as a legitimate research form. As part of the educational agenda in New Zealand since the 1840s when the first European settlers arrived, geography first became institutionalised in the high schools in the late 19th Century, reflecting the political and educational agendas of the time. The discourse on the institutionalisation of high school geography coincides with the later trajectory of university geography which took effect with the establishment of the first Department of Geography at Canterbury University College in 1937. Since then, the form and practice of geography have gone through considerable change. The perceived need to achieve ideological and methodological conformity affected both high school and university geography, providing a setting for some of the major contests in New Zealand geography. A documentation of 'how and why' change takes place and an insight into the underlying circumstances in contested matters, enables an understanding of the processes involved. It is only when one understands the milieu in which geography is set, that it is possible to articulate reasons for change. Geography in New Zealand grew to maturity, primarily through the six university departments. The activities of the agents working within the structural conditions of the university environment, reveal how the departments, individually and in concert, have been the sites of the more significant institutionalising activities, including the contemporary debates relating to feminist approaches and a sensitivity to a Maori perspective in geography. The community of academic and professional geographers have interacted with each other and with the larger sphere of society in the institutionalising actions by which this thesis measures institutionalisation. Reinforcing theory with practice, by revisiting the conditions of the structure and agency relationship, is essential to understanding institutionalisation which not only probes how geographical practice in New Zealand was initiated but how and why it is has been continuously reproduced and transformed. Apprehending this process suggests that the agents within New Zealand geography may benefit from an institutional appraisal of their discipline. A theoretically informed view of the way the discipline evolved, provides clues about conduct of future geographical practice.
Keywords: Institutionalisation; Geography education; Geographical practice